Airborne chloride deposit and its effect on marine atmospheric corrosion of mild steel. (August 2015) - Alcántara, J.; Chico, B.; Díaz, I.; de la Fuente, D.; Morcillo, M.
Highlights: Relationship between wave height, marine wind run and Cl − deposition rate. Salinity and steel corrosion obey an exponential decay function with shore distance. High salinity promotes coarser granulometry and less protective rust. High Cl − deposition rates give rise to high akaganeite and magnetite contents. Additional magnetite formation due to the transformation of lepidocrocite. Abstract: Research has been carried out for one year in six pure marine atmospheres with annual average chloride deposition rates of 70–1906 mg Cl − /m 2 day. A study of some environmental parameters and their influence in the airborne chloride deposit on the site has been accomplished. The paper also considers mild steel corrosion rate and the resulting corrosion products and layers, and its dependence of atmospheric salinity of the site. In addition to lepidocrocite and goethite, high akaganeite and magnetite contents were found in the corrosion products. Additional magnetite formation is possible due to the transformation of lepidocrocite.